A Review of Animal Models of Nonneoplastic Pancreatic Diseases. (January 2014) - Foster, John R.
The nonneoplastic diseases of the human pancreas generally comprise the inflammatory and degenerative conditions that include acute and chronic pancreatitis, with cystic fibrosis being arguably one of the most important diseases that induce the condition. Both acute and chronic conditions vary in severity, but both can be life threatening; and because of this fact, the study of their progression, and their responsiveness to therapy, is largely conducted by indirect means using serum markers of damage and repair such as amylase and lipase activities that normally occur at very low levels in the circulation but can be significantly increased during inflammatory episodes. Progress in the understanding the pathogenesis of both conditions has therefore been largely due to time course studies in animal models of pancreatitis, and it is in this context that animal model development has been so significant. In general terms, the animal models can be divided into the invasive, surgical procedures, and those induced by the administration of chemical secretagogues that induce hypersecretion of the pancreatic enzymes. The former include ligation and/or cannulation of the biliopancreatic ducts with infusion of solutions of various kinds, or the formation of closed duodenal loops. Secretagogue administration includes administration of caerulein orl -arginine in various protocols. An additional model involves administration of dibutyltin dichloride, which induces a partial blockage of the pancreatic ducts to induce pancreatic disease through enzymic reflux into the gland. The models have been invaluable in generating testable hypotheses for the human diseases. These hypotheses for the production of cellular damage as the initiating events in the disease include (1) intracellular chemical activation, (2) pancreatic secretion reflux, (3) intracellular production of reactive oxygen species, and (4) intracellular production of free radicals.